Essential Life Science : The Human Body - Melanie Waldron (Raintree, 2014)
The human body is an amazing machine, capable of great feats of strength, flexibility, and delicacy. It is made up of cells, tissues, organs, and systems, each with a job to do. This book will take readers on a tour of the human body, looking at all the incredible things it can do.
Keywords: Who We Are -- -Body Systems